Risk Factors of Monkeypox Outbreak in Indonesia: A Case-Control Study - Simanjorang, Chandrayani; Karima, Ulya Qoulan; Wangsawinangun, Rana Zahra Raniyah; Ariantini, Anggrahita Dwi; Fitri, Asti Elysia Rahmatul (Public Health of Indonesia, 2025)
Background: Monkeypox (Mpox) was declared a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO), and the first case in Indonesia was reported in 2022. Subsequently, there has been a significant increase in cases in 2023. Although global research on Mpox has expanded, particularly in regions like Europe and the Americas, there is a lack of studies focusing on the epidemiology and risk factors of Mpox in Southeast Asia, particularly in Indonesia. Objective: This study aimed to identify risk factors for the outbreak of Mpox in Indonesia. Methods: This study uses a case-control design method with purposive sampling. The study population was all people recorded in the Mpox screening system in Indonesia. All samples originated from the Mpox surveillance report for the Ministry of Health, Republic of Indonesia. The sample size was calculated using the Lemeshow formula with a 1:2 ratio. The total sample was 371 divided into 82 cases and 289 control groups. Results: The average age of participants was 30 years and most cases (96.3%) were male. Multivariate analysis revealed that individuals identifying as bisexual had a 10.8 times higher risk (OR: 10.87, 95% CI: 2.950–39.952) of contracting Mpox, and those identifying as gay had a 3.9 times higher risk (OR: 3.96, 95% CI: 1.238–12.671) compared to heterosexuals. Conclusion: This study concluded that sexual orientation was a significant risk factor in the incidence of Mpox in Indonesia. It is important to increase the uptake of Mpox vaccination among high-risk groups such as gays, bisexuals, and those in close contact with them. Keywords: risk factors; monkeypox; case-control; Indonesia